2014
DOI: 10.1007/s00402-014-2086-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes and quality of life in patients with osteosarcoma treated with amputation versus limb-salvage surgery: a systematic review and meta-analysis

Abstract: This meta-analysis including six high-quality studies indicates that amputation and limb-salvage surgery provide similar functional outcomes and quality of life for patients with osteosarcomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
3
43
1
1
Order By: Relevance
“…Complete surgical resection, if feasible, remains essential for cure [22]. Current surgical strategies focus on refining the nature and scope of resection to preserve uninvolved tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Complete surgical resection, if feasible, remains essential for cure [22]. Current surgical strategies focus on refining the nature and scope of resection to preserve uninvolved tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Extirpation of tumor tissue is expected to cause some degree of functional impairment; therefore, efforts should be made to decrease such impairment. Studies have reported on the functional outcomes of impairments on musculoskeletal tumor treatment [9,10,14,16,17,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, this system has been used in numerous studies to evaluate functional outcomes [9,10,14,16,17,19,22], making it one of the most widely used functional evaluation tools. The original scoring system was written in English and subsequently has been translated into Brazilian Portuguese and Japanese.…”
Section: Introductionmentioning
confidence: 99%
“…12 Limb salvage surgery patients have better quality of life without compromising survival than those who have undergone amputation. [13][14][15] Developments in adjuvant therapies, imaging diagnostics and surgical reconstructive techniques have made limb salvage surgery a preferred procedure for most primary sarcomas of the upper limbs with survival rates of 60-70%. 16,17 Today, major amputations are avoidable in most cases if the full potential of reconstructive possibilities is tapped.…”
Section: Discussionmentioning
confidence: 99%
“…13 The amputation of the upper arm would probably destroy the mental strength of the patient completely. For that reason, the preservation of the upper arm might be more emotionally acceptable than amputation, and the optimal method was en bloc resection and prosthesis implantation.…”
Section: Discussionmentioning
confidence: 99%